Upaya Penyempurnaan Alat Ukur: Analisis Validitas PAPI Kostick Item Revisi - Tarigan, Medianta; Fadillah (Faculty of Ushuluddin and Humanities, 2025)
This study aimed to evaluate the psychometric quality of the PAPI Kostick instrument in the Indonesian context through item revision, construct validity testing, and item-level analysis. The sample consisted of 1,289 respondents. Item revisions were conducted through linguistic and cultural adaptation to ensure semantic clarity and construct equivalence. Construct validity was examined using CFA, which demonstrated a good fit across all dimensions, with RMSEA values below 0.08. Most items were valid, with the highest proportion in Activity (100%). Further evaluation using the two-parameter logistic (2PL) IRT model indicated that 74–85% of items were located at the mid-range of the trait continuum, while discrimination indices were generally strong, with Activity achieving 100% in the normal category, followed by Leadership (89%). Overall, the revised version of PAPI Kostick demonstrated adequate construct validity, balanced item distribution, and satisfactory diagnostic properties, while continuous refinement remains necessary. Keyword: PAPI Kostick, validity, CFA, IRT